The Influence of Human Resource Development and Work Discipline on Employee Performance at PT Adelindo Perkasa Palembang City - Alpina Pebianti; Fauzia Afriyani; Try Wulandari (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of human resource development and work discipline on the performance of employees of PT Adelindo Perkasa. The method used is a quantitative method. The data in this study are primary data obtained from questionnaires that are processed using SPSS. Respondents totaled 51 employees, which were determined by the sample method using the saturated sampling method. The results of the t test analysis show that the variable human resource development (X1) and work discipline (X2) have a positive effect on employee performance (Y). However, the work discipline variable (X2) has a greater influence than the human resource development variable (X1). The Rsquare coefficient of determination is 0.872. This means that the contribution of human resource development and work discipline to employee performance is 87.2%. As for suggestions based on the results of research that has been carried out, it is hoped that this research will be useful as information material and input for employees of PT Adelindo Perkasa so that they can improve their performance, further enhance the development of human resources and work discipline.